Nuclear Energy as a Sustainable Source? Examining Media Discourses Surrounding the EU-Complementary Delegated Act (Communication & Society, 2024)
This paper contributes to the understanding of media discourses surrounding the sustainability of nuclear energy, particularly within a crisis context. The study examines the implications of the adoption of the Complementary Delegated Act on EU taxonomy by the European Commission on July 6, 2022, which officially categorises nuclear energy as sustainable. Employing a critical discourse analysis (CDA) methodology, the research explores the discourse strategies–nomination, predication, and argumentation– utilised across 695 news articles. The findings reveal the intricate representation of nuclear energy’s sustainability across the media. The Russian-Ukrainian conflict amplifies favourably the nuclear energy view as a reliable and sustainable energy source. However, the media discourse on nuclear energy’s sustainability reveals a variety of viewpoints. These varying outlooks provide essential insights for shaping effective energy policies. This research contributes valuable insights into understanding how media shapes and influences public perception of sustainability energy policies, amplifying specific actors’ voices and steering discourse toward distinct trajectories. Such insights are crucial in crafting energy policies.